Clumped methane isotopologues (13CH3D and 12CH2D2) of natural samples measured using a high-resolution mass spectrometer with an improved pretreatment system. Issue 1 (6th December 2022) - Wang, Xinchu; Liu, Cong-Qiang; Zhang, Naizhong; Xu, Sheng; Pang, Zhiyong; Li, Si-Liang; Ding, Hu; Chen, Jianfa; Xie, Zengye; Ellam, Rob M.
Abstract : This work is dedicated to improving the efficient purification, collection, and clumped isotope analysis method for natural methane with a wide range of concentrations. Abstract : Doubly-substituted methane isotopologues ( 13 CH3 D and 12 CH2 D2 ) can provide unique information to resolve the origin, transport, and conversion of environmental methane. We used a high-resolution mass spectrometer (Thermo Fisher Scientific 253 Ultra) to precisely determine Δ 13 CH3 D and Δ 12 CH2 D2 (precision and accuracy of ∼0.35‰ and ∼1.35‰ (1 σ ), respectively) in this study. The impacts of temperature, humidity, and slit quality are found to be critical for the reproducibility of the results, while the fragmentation rate and bellows effects on the clumped isotope results were negligible. A heating equilibrium experiment performed at 500 °C, 400 °C and 300 °C ( n = 19) calibrates the results to an absolute reference. A pretreatment system that can extract methane having concentrations from ∼15% to ∼99.8% is proposed, while the fractionation produced throughout the pretreatment is negligible within precision (Δ 13 CH3 D = +0.16 ± 0.32‰ and Δ 12 CH2 D2 = +0.14 ± 1.12‰ ( n = 16)). Analyses of natural gases from shale basins and variable methane-rich gases emitted from artificial lakes validate the capability of the current pretreatment and spectrometer systems to determine methane clumped isotopes in a wide range of natural environmental samples.